Optimal Taxation with Rent-Seeking - Casey Rothschild; Florian Scheuer (Center for Economic Studies and ifo Institute (CESifo), 2014)
We develop a framework for optimal taxation when agents can earn their income both in traditional activities, where private and social products coincide, and in rent-seeking activities, where private returns exceed social returns either because they involve the capture of pre-existing rents or because they reduce the returns to traditional work. We characterize Pareto optimal non-linear taxes when the government does not observe the shares of an individual's income earned in each of the two activities. We show that the optimal externality correction typically deviates from the Pigouvian correction that would obtain if rent-seeking incomes could be perfectly targeted, even at income levels where all income is from rent-seeking. If rent-seeking externalities primarily affect other rent-seeking activity, then the optimal externality correction lies strictly below the Pigouvian correction. If the externalities fall mainly on the returns to traditional work, the optimal correction strictly exceeds it. We show that this deviation can be quantitatively important.
Keywords: 330; rent-seeking; tax policy; multidimensional screening